Impact of a consortium-based student mobility programme: The case of AIMS (Asian International Mobility for students) - Naoki Umemiya; Miki Sugimura; Romyen Kosaikanont; Nordiana Mohd Nordin; Abdul Latiff Ahmad (Emerald Publishing, 2024)
Purpose - This paper discusses the effectiveness of a consortium-based student mobility programme by investigating the impact of the Asian International Mobility for Students (AIMS) Programme. AIMS is a regional multilateral large-scale student mobility programme based on a consortium of 10 member countries and 87 member universities with the Southeast Asian Ministers of Education Organization Regional Centre for Higher Education and Development (SEAMEO RIHED) as a facilitator. Over 6,000 students have participated in a semester-long intra-regional student exchange under AIMS since 2010. Design/methodology/approach - The study employed questionnaire surveys and semi-structured interviews to investigate the impact of AIMS and its advantages as a consortium-based student mobility programme. Findings - It was found that AIMS significantly impacted member universities by accelerating their internationalisation processes through increasing the number of inbound and outbound students and courses offered in English and so on. AIMS has promoted harmonisation among the members by developing common procedures and guidelines, providing platforms for mutual sharing of experiences and good practices and capacity building of international relations offices. AIMS has also had a significant impact on students by enhancing their regional identity and knowledge about the region of Asia, contributing to their development as future regional and global citizens. As advantages of AIMS, member universities efficiently built a foundation for international collaboration with common procedures and guidelines and shared their experiences through such venues as Annual Review Meetings. Students also feel supported by having clear guidance and find programmes prepared by host universities and SEAMEO RIHED useful. Originality/value - This study is unique in that it empirically studies the impact of one of Asia's largest student mobility programmes for the first time by analysing large-scale qualitative and quantitative data.